Delegation of Work Within a Patient-Centered Medical Home. (December 2022) - Wakefield, Bonnie J.; Lampman, Michelle A.; Paez, Monica B.; Farag, Amany; Ferguson, Heidi; Stewart, Greg L.
Abstract : OBJECTIVE: The aim of this study was to analyze the perceptions of core team members implementing patient-centered medical home (PCMH) within the Veterans Health Administration regarding delegation of work. BACKGROUND: Significant overlap exists in the performance of work tasks among PCMH team members (primary care providers, RNs, clinical associates, clerks), and scant literature exists on appropriate delegation within PCMH teams. METHODS: This study conducted used a quantitative and qualitative analysis of 4254 respondents to a 2018 survey. RESULTS: Primary care providers rely heavily on team members, and nurses report being relied upon at high levels. Lack of role clarity and a perceived need for a team leader were concerns voiced by participants. CONCLUSIONS: Findings indicated a need for clear guidance on roles and responsibilities within the team. Patient-centered medical home team members need information about the scope of practice of each professional group to allow providers to function at the top of their scope of practice and ensure effective delegation.